1995
DOI: 10.1177/1073191195002003007
|View full text |Cite
|
Sign up to set email alerts
|

Confirmed Attorney Coaching Prior to Neuropsychological Evaluation

Abstract: Even though it has been speculated that attorneys might educate or "coach" their clients prior to forensic neuropsychological examinations, there have been no documented instances of this to date. It might be particularly tempting for attorneys to coach their clients on symptom validity scales. A case in which it was strongly suspected that attorney coaching had occurred is presented. The attorney representing the patient actually admitted to an administrative law judge that he had educated his client prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(58 citation statements)
references
References 13 publications
0
57
0
1
Order By: Relevance
“…The employment of sophisti- cated methods to reveal negative response bias and knowledge that such techniques exist may in turn result in claimants being increasingly better prepared by their lawyers. However, a complex assessment strategy based on a multi-method approach rather than a single test is, of course, much more difficult to beat (for an illustrative case, see the report by Youngjohn 1995). The percentage of patients with alleged PTSD symptoms who were suspected of having negative response bias in this study (70%) was also higher than the rate recently reported by Stevens et al (2008) from a sample which basically stemmed from the same population, with a comparable referral background, and the same forensic examiner.…”
Section: Discussionmentioning
confidence: 99%
“…The employment of sophisti- cated methods to reveal negative response bias and knowledge that such techniques exist may in turn result in claimants being increasingly better prepared by their lawyers. However, a complex assessment strategy based on a multi-method approach rather than a single test is, of course, much more difficult to beat (for an illustrative case, see the report by Youngjohn 1995). The percentage of patients with alleged PTSD symptoms who were suspected of having negative response bias in this study (70%) was also higher than the rate recently reported by Stevens et al (2008) from a sample which basically stemmed from the same population, with a comparable referral background, and the same forensic examiner.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropsychological examinees in civil litigation seem more likely to have attorneys who are more invested in knowing the nature and purpose of psychological tests administered to their clients, to the point that some coach their clients in how to take the tests (Wetter & Corrigan, 1995;Youngjohn, 1995). Most criminal defense attorneys are probably less knowledgeable about or less involved in the process of assessing cognitive capacities than attorneys involved in civil litigation on brain injury issues.…”
Section: Differences Between Populationsmentioning
confidence: 94%
“…Participants in the malingering condition may be educated about PTSD criteria, or may be educated about the validity scales of the MMPI-2. Such coaching has been examined because some lawyers educate their clients about the MMPI-2 scales before the clients undergo psychological assessment (Rosen, 1996;Youngjohn, 1995). Research indicates that validity indicators such as the F tests can generally distinguish between malingered and genuine PTSD (e.g., Bury & Bagby, 2002;Elhai et al, 2002Elhai et al, , 2004.…”
Section: Psychological Inventoriesmentioning
confidence: 97%
“…However, parents may coach a child to report symptoms that the child does not have, or to exaggerate complaints (Lubit, Hartwell, van Gorp, & Eth, 2002). Coaching similarly can occur in adults, as illustrated by cases in which attorneys have coached their clients to report symptoms (Aronson, Rosenwald, & Rosen, 2001;Youngjohn, 1995).…”
mentioning
confidence: 95%